Wykorzystanie analizy skupień w prognozowaniu analogowym - Kołaszewska, Urszula (The Usage of Cluster Analysis in Analogy Forecasting, 2005)
In work a spacial-time analogy method was applied for issuing a forecast factors influencing e-commerce development in Poland. In order to choose pattern objects for forecasted object, a cluster analysis and ranking were carried out. Out of the group of countries classified as the best prepared there were chosen countries similar to Poland. The similarity of objects was estimated on the basis of the shape criterion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 248-256